Pengembangan Modul Penyusunan Soal Higher Order Thinking Skills Berorientasi AKM pada Mata Pelajaran IPA SD untuk Meningkatkat Literasi Sain Siswa - Rima Yanti Z; Irwan Koto; Endang Widi Winarni (UNIB Press, 2022)
Abstract This study aims to describe the development, feasibility, and determine the effectiveness of the AKM-oriented HOTS question formulation module in elementary science subjects and to determine student literacy achievements in answering AKM-oriented HOTS questions in elementary science subjects. This research is a development research using the ADDIE model. Analysis of teacher needs for the module, initial module design, module development, module implementation, and evaluation. Data were collected through surveys, documentary analysis, teacher response interviews, and student literacy tests. The survey was conducted using a questionnaire to determine the teacher's needs for the HOTS question preparation module. The instruments used are expert validation instruments, question analysis instruments, and test instruments to determine student literacy achievements. The results of this study are the compilation of HOTS questions that are feasible to use as evidenced by the value of the material expert's reliability test results of 0.58, media experts 0.435, and linguists 0.696. The module is effective for improving the ability of teachers in preparing HOTS questions as evidenced by the T-Test score with a significance level of 0.04 (p < 0.05).